A inter-relação entre as infecções pulpares e a diabetes - Azuma, Mariane Maffei [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Diabetes is a metabolic disease that affects the dental pulp due to some local changes. Before this information, a research through literature was made with the purpose to study the interrelation between pulp infections and diabetes. We analyzed several articles that described researches involving animals and they showed that there is a relation between diabetes and size, progression and severity of the periradicular lesions. There is evidence that diabetes is an important factor over the oral tissue, causing alterations in the inflammatory mediators and changing the structure of the pulp. Although many studies prove that there is an interrelation between diabetes and pulp infections, there are still some gaps in the current literature that need to be filled

A diabetes é uma doença metabólica que afeta a polpa dentária em função de algumas alterações locais. Diante disso, foi realizada uma revisão de literatura com a finalidade de estudarmos a inter-relação entre as infecções pulpares e a diabetes. Revisamos vários artigos, onde a pesquisa foi feita em animais, e os resultados mostraram que há relação entre a diabetes e o tamanho, progressão e severidade de lesões perirradiculares. Há evidências de que a diabetes é um fator crítico sobre os tecidos orais, resultando na alteração de mediadores inflamatórios e modificação dos componentes estruturais da polpa. Embora vários estudos comprovem a inter-relação entre as infecções pulpares e a diabetes, ainda existem várias lacunas na literatura atual que precisam ser preenchidas
Keywords: Diabetes mellitus; Polpa dentária; Tratamento do canal radicular